An Examination of Middle School Students’ Mathematical Bullying Victimization Levels in Relation to Socio-Demographic Variables - Kucukgencay, Naci; Peker, Bilge (International Journal of Academic Studies in Science and Education, 2024)
This study aimed to examine mathematical bullying victimization among middle school students and its relationship with socio-demographic variables using the Mathematical Bullying Victimization Scale (MBV-S). The sample consisted of 493 middle school students selected using a disproportionate stratified sampling method from five different schools in Konya, Türkiye, during the spring semester of the 2021-2022 academic year.Data were collected using the relational screening model and analyzed with nonparametric statistical methods. The results showed that female students were more frequently subjected to mathematical bullying compared to males. No significant differences were found in MBV-S scores based on grade levels. However, the analysis of school types revealed that students in girls-only religious middle schools experienced higher levels of mathematical bullying than students in other types of schools. Additionally, students with below-average mathematics achievement were more likely to be victims of mathematical bullying, whereas students with above-average achievement reported lower levels of victimization. The findings highlight the importance of developing strategies to address mathematical bullying that consider students’ mathematical abilities and social dynamics. Supportive and inclusive environments should be prioritized, particularly for students with low achievement and those in specific school settings.